Pengaruh Kompetensi dan Komunikasi Terhadap Kinerja Karyawan PT Beta Pharmacon - Sulistyaningsih; Sari Marliani; July Yuliawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Performance is the work result that can be achieved by individuals or work teams within an organization to achieve organizational goals within a certain period of time. Competence is defined as an individual's ability to carry out a job correctly and with excellence. Reciprocal activities in conveying messages, using message delivery media or without media, are defined as communication processes. This research aims to determine and analyze the influence of competency and communication variables on the performance of PT Beta Pharmacon. The quantitative descriptive research design used multiple linear regression verification a population of 388 employees, and used a proportional starting random sampling technique with the Slovin formula and a sample of 80 was determined. The results of the descriptive analysis of the competency are in good criteria, the communication is in good criteria and the performance is in good criteria. The results of the verification analysis of the competency variable (X1) partially have a very significant influence on employee performance, the communication variable (X2) partially has a very significant influence on employee performance, while the competency variable (X1) and communication variable (X2) have a simultaneous influence on employee performance (Y).